Unsteady Magnetohydrodynamic Slip Flow, Heat and Mass Transfer over a Permeable Stretching Cylinder with Soret and Dufour Effects in Porous Medium - Jamir, Temjennaro; Konwar, Hemanta (Diffusion and defect data. Solid state data. Pt. A, Defect and diffusion forum, 2023)
This study considers the unsteady magnetohydrodynamic slip flow past a permeable stretching cylinder by taking into account the Soret and Dufour effects. Using similarity transformations, the partial differential equations governing the flow, heat, and mass transfers are transformed into a system of ordinary differential equations. These equations are numerically solved for a variety of governing parameter values using the boundary value problem solved package, bvp4c, which is available in the MATLAB software. The outcomes of the governing parameters on the skin friction coefficient, Nusselt and Sherwood numbers are also examined. Upon observation, the unsteadiness parameter influences a positive growth on the momentum, thermal and concentration boundary layers. Slip parameter can be enhanced to improve the friction drag force about 28% and the rate of cooling around 3%. Also, larger effects of Dufour leads to around 9% decay in heat transfer rate and Soret effect to cause around 11% drop in mass transfer rate. Comparison with existing results show excellent agreement which justifies the reliability of the obtained results.